Provably secure quantum resistance two-server password-authenticated key exchange protocol - Anqi YIN; Yuanbo GUO; Ding WANG; Tongzhou QU; Lin CHEN (Tongxin xuebao)
Aiming at the problem that the lattice-based single-sever password-authenticated key exchange (PAKE) protocols are not resistant to server compromise attack, while the existing lattice-based multi-server PAKE protocols are inefficient and incompatible with two-server scenarios.The first lattice-based two-party smooth projective hash function (SPHF) was proposed by utilizing the learning with errors (LWE), which was indistinguishability under adaptive chosen-ciphertext attack(IND-CCA2) secure.The parameters of the based public key encryption (PKE) scheme were also identified.On this basis, pertinent two-server PAKE protocols from lattices were designed countering both passive and active attackers.The two quantum resistance protocols were able to achieve password-only settings and the expensive cryptographic primitives were not used, including signature/verification, fully homomorphic encryption and secret sharing.The utilization of zero knowledge proofs were avoided by the protocol under the passive attackers.In the standard model, rigorous security proofs were provided for the two proposed protocols.Experimental results show that the proposed SPHF and PAKE protocols exhibit higher execution efficiency.